POLICIES OF SPIN-OFF REGARDING SHARIA BUSINESS UNIT OF PT. BNI IN INDONESIA - Afif Alamsyah Makarao (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
Acceleration of the development of Sharia business will be more easily done throughSharia Banks. With the separation of Sharia Business Unit into Sharia Banks it willhopefully be easier to compete, more agile and flexible in making business decisions inthe future. Improve the quality of trust and image as Sharia Bank; by separating theexpected bank that is formed will have a high reputation and a deep understanding ofsharia products and services. Increase productivity and efficiency, Separation is donealso expected to encourage the passage of market best practice and good corporategovernance (GCG) in business management of Sharia Banks. Easier In Improving thecapital structure, by doing the separation, Sharia Banks can conduct effective strategiccooperation with third parties, including related to the capital increase if needed in orderto anticipate future business opportunities. Providing benefits to shareholders, Theresults of the separation of UUS into Sharia Banks is believed to have a positive impacton shareholder value as well as in the form of dividends to bank shareholders whoperform the separation. Support the growth rate of Islamic banking, Sharia Bank Plan inaccordance with the business plan has been prepared, the separation of bank assetgrowth is expected to rise and contribute significantly to the growth of Islamic bankingindustry. Improve financial performance as reflected in the Consolidated FinancialStatements.